Cullin 3 targets the tumor suppressor gene ARMC5 for ubiquitination and degradation. Issue 4 (April 2020) - Cavalcante, Isadora Pontes; Vaczlavik, Anna; Drougat, Ludivine; Lotfi, Claudimara Ferini Pacicco; Perlemoine, Karine; Ribes, Christopher; Rizk-Rabin, Marthe; Clauser, Eric; Fragoso, Maria Candida Barisson Villares; Bertherat, Jérôme; Ragazzon, Bruno
Abstract : ARMC5 (Armadillo repeat containing 5 gene) was identified as a new tumor suppressor gene responsible for hereditary adrenocortical tumors and meningiomas. ARMC5 is ubiquitously expressed and encodes a protein which contains a N-terminal Armadillo repeat domain and a C-terminal BTB (Bric-a-Brac, Tramtrack and Broad-complex) domain, both docking platforms for numerous proteins. At present, expression regulation and mechanisms of action of ARMC5 are almost unknown. In this study, we showed that ARMC5 interacts with CUL3 requiring its BTB domain. This interaction leads to ARMC5 ubiquitination and further degradation by the proteasome. ARMC5 alters cell cycle (G1/S phases and cyclin E accumulation) and this effect is blocked by CUL3. Moreover, missense mutants in the BTB domain of ARMC5, identified in patients with multiple adrenocortical tumors, are neither able to interact and be degraded by CUL3/proteasome nor alter cell cycle. These data show a new mechanism of regulation of the ARMC5 protein and open new perspectives in the understanding of its tumor suppressor activity.